Constantly Bombarded with New Drugs: What’s a Cardiologist to Do? - Albert E. Raizner; James B. Young (Methodist DeBakey Cardiovascular Journal)
Every physician encounters a barrage of direct-to-consumer and direct-to-physician advertising and is faced with the daunting task of deciding which drugs to add to their clinical armamentarium and how and when to add them. The purpose of this Points to Remember is to present a commonsense approach to incorporating newer drugs, or perhaps new indications for older drugs, into our clinical practice. To illustrate these points, this article focuses on a single drug, empagliflozin, a sodium-glucose cotransporter-2 (SGLT-2) inhibitor that has been highly marketed in lay and medical media and hence has been incorporated into professional society treatment guidelines.